Effect of micelles, microemulsions and other supramolecular aggregates on the hydrolysis of β-lactam antibiotics - Oliveira, Anselmo Gomes de [UNESP]; Scarpa, M. V. [UNESP] (My University, 1999)
A critical revision of the literature was made regarding the stability of β-lactam antibiotics in the presence of surfactants. The factors involved in the drug decomposition were analyzed in the development of the discussion. The analysis has indicated that some organized systems obtained from surfactants can be used to control rates and mechanisms of antibiotic decomposition. These organized systems can also be used to obtain specific information about the drug reactivity in a microenvironment similar to the site of pharmacological effect.
Keywords: β-lactam antibiotics; Drug decomposition; Micelles; Microemulsions; Surfactants; amoxicillin; ampicillin; beta lactam antibiotic; cefaclor; cefadroxil; cefalexin; cefazolin; cefradine; cephalosporin derivative; cetrimide; dodecyl sulfate sodium; penicillin derivative; penicillin G; polidocanol; propicillin; surfactant; drug decomposition; drug hydrolysis; drug stability; drug structure; ionic strength; micelle; microemulsion; pH; review